A Paleoenvironmental Reconstruction of Elkwater Lake, Alberta - Wiseman, Dion; Running, Garry; Freeman, Andrea (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractCores retrieved from two slump blocks at the west end of Elkwater Lake, Alberta were used to determine which of two mass wasting events was responsible for impounding the lake and to establish a maximum age of lake formation. A high resolution Digital Elevation Model of the study area was used to estimate the volume of material involved in each mass wasting event, recreate pre-slump topographic conditions, determine the probable extent and elevation of the lake at different periods in time, and evaluate the viability of alternative outlets. Results suggest that the lake formed no more than 9440 BP as a result of impoundment by the eastern slump block. The lake rose to its highest mid-Holocene elevation prior to 7245 BP, establishing an outlet through Feleski Creek 3.5 km northeast of the present shoreline. Lake levels then dropped during the comparatively dry Altithermal, concurrent with a period of rapid sediment influx and the development of the alluvial fan on which the Stampede site is located. As water levels rose during the late Holocene, and with the former outlet cut off by progradation of the alluvial fan, Elkwater Lake established its present outlet though Ross Creek.